Simulating progressive damage of notched composite laminates with various lamination schemes - Mandal, Bibekananda; Chakrabarti, Anupam (Zielona Góra: Uniwersytet Zielonogórski)
A three dimensional finite element based progressive damage model has been developed for the failure analysis of notched composite laminates. The material constitutive relations and the progressive damage algorithms are implemented into finite element code ABAQUS using user-defined subroutine UMAT. The existing failure criteria for the composite laminates are modified by including the failure criteria for fiber/matrix shear damage and delamination effects.
Keywords: damage mechanics; user-defined subroutine; composite laminates; finite element; strength; degradation